Does state ownership facilitate outward FDI of Chinese SOEs? Institutional development, market competition, and the logic of interdependence between governments and SOEs. Issue 1 (February 2017) - Huang, Yuanyuan; Xie, En; Li, Yu; Reddy, K.S.
Highlights: Drawing on resource dependence theory, this study reveals the dark-side effects of state ownership on manufacturing SOEs' OFDI from EE. A high percentage of state-owned shares is negatively associated to EE manufacturing SOEs' OFDI. Relative to local manufacturing SOEs, central manufacturing SOEs in EE are less likely to engage in OFDI. Institutional development and market competition weaken the negative relationship between the percentage of state-owned shares and SOEs' OFDI, in both independent and joint patterns. Abstract: Outward foreign direct investment (OFDI) of manufacturing state-owned enterprises (SOEs) from emerging economies (EE) has emerged as a significant phenomenon in global markets. Although previous research has emphasized the bright-side of state ownership in facilitating SOEs' OFDI, the stream of research largely overlooks its dark-side effects. Drawing on resource dependence theory (RDT), we argue that state ownership creates dependence of SOEs on their home governments, which may undermine manufacturing SOEs' willingness to conduct OFDI, autonomy and market orientation, and legitimacy in overseas markets. Thus, substantial state ownership may counteract with manufacturing SOEs' OFDI from EE. Our empirical results, based on a sample of 507 Chinese publicly-listed manufacturing SOEs during 2007–2013, show that a high percentage of state-owned shares exerts negative effects on SOEs' OFDI. Relative to local SOEs, central SOEs are less likely to engage in OFDI. Further, the negative effect of the percentage of state-owned shares on SOEs' OFDI will be alleviated by institutional development and competition intensity. The study contributes to literature by making a real theoretical case for the dark-side effects of state ownership on manufacturing SOEs' OFDI from EE.